2011
DOI: 10.2224/sbp.2011.39.10.1303
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Motivations of Students Taking Professional Certificate Examinations

Abstract: In this study we explored the attitudes and motives of business studies students taking examinations for professional certificates, where their participation may have a cognitionoriented motive. The study was divided into 2 phases: in the first phase, a questionnaire survey was used to examine the differences between internal and external encouragement perspectives for those students with and without professional certificates. We found that the intrinsic motivation of students with professional certificates wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 19 publications
3
14
0
1
Order By: Relevance
“…The results are also compatible with most of the studies which are carried out in different countries and different samples, from which it can be generally infers that motivation has an important effect on academic performance in a positive way (Goodman, Jaffer, Keresztesi, Mamdani, Mokgatle, Musariri, Pires, Schlechter, 2011;Mo, 2011;Cheng, Lin and Su, 2011;Ming, Ling and Jaafar, 2011;Nishitani and Matsuda, 2011). As Ryan and Deci (2000) argue, 'to be motivated means to be moved to do something'.…”
Section: Resultssupporting
confidence: 88%
“…The results are also compatible with most of the studies which are carried out in different countries and different samples, from which it can be generally infers that motivation has an important effect on academic performance in a positive way (Goodman, Jaffer, Keresztesi, Mamdani, Mokgatle, Musariri, Pires, Schlechter, 2011;Mo, 2011;Cheng, Lin and Su, 2011;Ming, Ling and Jaafar, 2011;Nishitani and Matsuda, 2011). As Ryan and Deci (2000) argue, 'to be motivated means to be moved to do something'.…”
Section: Resultssupporting
confidence: 88%
“…Consequently, although the results of the research by Cheng et al (2011) indicated that students were more frequently motivated Journal of Hospitality & Tourism Education 2015.27:112-119.…”
Section: Introductionmentioning
confidence: 93%
“…In terms of faculty members' views of hospitality industry certifications, Damitrio and Schmidgall (2001) investigated how certification in the financial area of hospitality management was received by those who taught financial management courses in the hospitality field and found that faculty views were mixed. Furthermore, results of a study concerned with students' perceptions of certifications conducted by Cheng, Lin, and Su (2011) showed that students were often intrinsically motivated rather than extrinsically motivated to earn certifications, yet faculty support and encouragement toward students helped them prepare for examinations by creating a more positive outlook and attitude.…”
Section: Introductionmentioning
confidence: 99%
“…McLaughlin [8] and Newton et al [9] report the need to ascertain the relationship between motivation and how it relates to student success within their particular career choices. Cheng et al [10] asserts the need to enhance motivation as a means to bolster student success within the arena of high stakes testing, such as the Nurse Aid Competency Examination. Therefore, it is essential to determine how motivation, as measured by Vroom's Expectancy Theory, leads to academic achievement and provides a qualified workforce of certified nurse assistants for the nation's health care centers.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the relationship between motivation and academic achievement is critical within the educational arena [10]. By identifying factors that nurture motivation, instructors and administrators within institutions of higher learning may positively influence student academic achievement [23].…”
Section: Introductionmentioning
confidence: 99%